6-h advances alter circadian activity patterns, fasting glucose, and insulin levels in C57BL6/J mice. Issue 1 (2nd January 2016) - Nascimento, Nara F.; Hicks, Jasmin A.; Carlson, Karen N.; Hatzidis, Aikaterini; Amaral, Danielle N.; Seggio, Joseph A.
Abstract : Chronobiological disruptions, including shift work, have been linked to a number of disorders such as fatigue and diabetes. Additionally, there is evidence to support that exercise cannot only counteract fatigue and the onset of diabetes, but also alleviate the other negative symptoms associated with shift work. Therefore, the present study investigated the effects of wheel running and monthly 6-h phase advances on the circadian locomotor activity patterns and glucose and insulin levels in C57BL6/J mice. 6-h phase advances produced decreases in fasting glucose and increases in insulin, and wheel-running was able to alleviate the spike in insulin secretion. Additionally, mice experiencing the shift increased their food intake, despite having no change in body mass. Circadian wheel-running activity was also altered in phase-advanced mice. These results provide further evidence that chronobiological disruptions can lead to alterations in physiology and behavior, and that exercise can alleviate some of those symptoms.